The ocean's role in global change : progress of major research programs - National Research Council (U.S.). Ocean Studies Board; Merrell, William (Washington, DC : National Academy Press, 1994)
Provides summaries on the progress of the major oceanographic research programs. This book looks at programs that study processes that occur over periods ranging from days to hundreds of years - the contemporary system, and those that seek to understand long-term variations ranging from thousands to millions of years - the geological perspective.
The Ocean's Role in Global Change: Progress of Major Research Programs -- Copyright -- Contents -- Preface -- The Ocean's Role in Global Change: Progress of Major Research Programs -- Introduction -- The Contemporary System -- GLOBAL OCEAN OBSERVING SYSTEM -- TROPICAL OCEAN-GLOBAL ATMOSPHERE PROGRAM -- Summary -- WORLD OCEAN CIRCULATION EXPERIMENT -- Summary -- JOINT GLOBAL OCEAN FLUX STUDY -- Summary -- GLOBAL OCEAN ECOSYSTEM DYNAMICS -- Summary -- ATLANTIC CLIMATE CHANGE PROGRAM -- ARCTIC SYSTEMS SCIENCE -- ACOUSTIC THERMOMETRY OF OCEAN CLIMATE PROJECT -- A GLOBAL OCEAN-ATMOSPHERE-LAND SYSTEM FOR SEASONAL-TO-INTERANNUAL CLIMATE PREDICTION PROGRAM -- LAND- OCEAN INTERACTIONS IN THE COASTAL ZONE -- The Geological Perspective -- OCEAN DRILLING PROGRAM -- Summary -- RIDGE INTER-DISCIPLINARY GLOBAL EXPERIMENTS -- Summary -- THE GLOBAL CHANGE AND CLIMATE HISTORY PROGRAM OF THE U.S. GEOLOGICAL SURVEY -- MARINE ASPECTS OF EARTH SYSTEM HISTORY -- Summary -- Crosscutting Issues -- PLATFORMS FOR OBSERVATION AND COLLECTION -- LONG TIME SERIES -- SATELLITES -- DATA MANAGEMENT AND AVAILABILITY -- Conclusions -- Appendix I-List of Acronyms -- Appendix II-Parameters of Importance for Understanding the Ocean's Role in Global Change 1 -- Appendix III-Bibliography, Program Documents, and Addresses -- OCEAN STUDIES BOARD CONTACTS -- GENERAL PUBLICATIONS -- GOOS -- Contact -- Publications -- TOGA -- Contacts -- Publications -- WOCE -- Contacts -- Publications -- JGOFS -- Contacts -- Publications -- GLOBEC -- Contacts -- Publications -- ACCP -- Contact -- Publications -- ATOC -- Contact -- Publications -- GOALS -- Contacts -- Publications -- LOICZ -- Contacts -- Publications -- ARCSS -- Contacts -- Publications -- ODP -- Contacts -- Publications -- RIDGE -- Contact -- Publications -- USGS GLOBAL CHANGE -- Contact -- Publications -- MESH -- Contacts -- Publications.
Board chairman: William Merrell, Jr.
Work was sponsored by the National Oceanic and Atmospheric Administration's Office of Global Programs through the National Science Foundation grant no. OCE-9313563-R.
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: Ocean-atmosphere interaction -- Research -- United States; Interaction mer-atmosphère -- Recherche -- États-Unis.; SCIENCE -- Earth Sciences -- Oceanography; NATURE -- Ecosystems & Habitats -- Oceans & Seas; Ocean-atmosphere interaction -- Research; United States; Interaction mer-atmosphère -- Recherche -- États-Unis.